Fuzzy Logic Tsukamoto untuk Menentukan Jenis Penyakit Hipertensi dengan Golongan Obat Yang Sesuai - Jasri . (RJOCS (Riau Journal of Computer Science), 2018)
Patients with hypertension disease is a degenerative disease that emerges unconsciously. Factors that cause hypertension can occur due to heredity, age, wrong diet, lack of activity, lifestyle and mind or stress. Fuzzy logic uses the Stukamoto method to determine what drugs fit the type of hypertension, to keep blood pressure under control.